Complex dilemmas in group therapy : pathways to resolution - Motherwell, Lise, 1955-; Shay, Joseph J. (New York : Routledge, Taylor & Francis Group, 2014)
'Group work presents the therapist with many situations, considerations, and, ultimately, decisions that are unique to the practice of group psychotherapy. Complex Dilemmas in Group Therapy includes advice and insights from more than fifty of the most eminent group therapists in the world and is edited by two leading thinkers and practitioners in the field. In its pages clinicians will find expert guidance on some of the most difficult situations group therapists face, and they'll come away from the book with a host of practical strategies for facilitating their work as well as deeper and broader understanding of the overarching ideas that underpin the practice of successful group therapy'--
'Complex Dilemmas in Group Therapy includes advice and insights from more than 25 of the most eminent group therapists in the world and is edited by two leading thinkers and practitioners in the field'--
Includes bibliographical references and index.
Keywords: Group psychotherapy -- Methodology; Group psychotherapy -- Case studies